HATE SPEECH ON SOCIAL MEDIA: WITTGENSTEIN’S LANGUAGE GAMES THEORY - Rizkia Shafarini; Dadan Rusmana (Universitas Muhammadiyah Surakarta, 2022)
One of the most prevalent concerns on social media is hate speech. Because hate speech is mainly transmitted in text form on social media, linguistic analysis is required to determine the meaning of the hate speech. This study aims to look at the view of hate speech on social media using a literature study technique based on the Wittgenstein language game theory approach. According to Wittgenstein, language does not have a single logical structure but is complicated in its use in human life, which spans a wide range of activities. Previous research has looked at the meaning linked with language use in social media. As Wittgenstein proposes, the finding of the research is That ordinary language collected through social media data may be utilized to offer direct answers to social scientific questions. Online media that allows people to represent themselves and cooperate to share, connect with other users, and form virtual social relationships are referred to as social media. Starting with the presentation of quotes, there will be a